2006
DOI: 10.1038/nm1359
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 rescues tolerant CD8+ T cells for use in adoptive immunotherapy of established tumors

Abstract: CD8+ T cells can mediate eradication of established tumors, and strategies to amplify tumor-reactive T-cell numbers by immunization or ex vivo expansion followed by adoptive transfer are currently being explored in individuals with cancer. Generating effective CD8+ T cell-mediated responses to tumors is often impeded by T-cell tolerance to relevant tumor antigens, as most of these antigens are also expressed in normal tissues. We examined whether such tolerant T cells could be rescued and functionally restored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 35 publications
7
174
0
Order By: Relevance
“…Nevertheless, homeostatic proliferation was able to prevent hyporesponsiveness of antitumor T cells and also to reverse established hyporesponsiveness of peptide-anergized 2C cells, so the homeostatic proliferation process maintained and/or restored T cell function in both settings. Consistent with our results, a recent report has indicated that exogenous IL-15 also can reverse T cell anergy in vivo (57).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, homeostatic proliferation was able to prevent hyporesponsiveness of antitumor T cells and also to reverse established hyporesponsiveness of peptide-anergized 2C cells, so the homeostatic proliferation process maintained and/or restored T cell function in both settings. Consistent with our results, a recent report has indicated that exogenous IL-15 also can reverse T cell anergy in vivo (57).…”
Section: Discussionsupporting
confidence: 93%
“…These CD44 hi CD122 hi CD8 ϩ T cells may have functions in the immunosurveillance of tumor cells. Teague et al (28) described the ability of IL-15-cultured CD8 ϩ T cells to inhibit tumor growth. In their interpretation, IL-15 overcame immunotolerance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…FBL, a Friend virus-induced erythroleukemia of C57BL/6 (H-2 b ) origin that expresses MHC class I and FMuLV Gag-encoded products, has been previously described (61). The FMuLV Gag peptide (CCLCLTVFL) recognized by TCRgag CD8 + T cells was purchased from Pi Proteomics.…”
Section: Methodsmentioning
confidence: 99%